2017
DOI: 10.5812/traumamon.61871
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Accidents in Tehran Emergency Medical Service During 2012 to 2013

Abstract: Background: There is a lack of epidemiological data on emergency Medical service (EMS) missions for accidents in Iran. The present study aimed at obtaining representative data on the epidemiology of emergency Medical service missions for of accidents in Tehran, during years 2012 to 2013. Methods: Active EMS stations in Tehran were selected through stratified random sampling in different regions of the city during a twelve-month period from March 2012 to March 2013. Data was collected through a questionnaire on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Likewise, previously published papers in Iran and other countries show that road traffic accidents are usually recorded more in younger subjects than in older ones. It seems that the increased risk of accidents in this age group is due to the need for travel to perform a living or education in young people, their little experience of driving, unnecessary acceleration, and finally inadequate knowledge of traffic rules and regulations (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, previously published papers in Iran and other countries show that road traffic accidents are usually recorded more in younger subjects than in older ones. It seems that the increased risk of accidents in this age group is due to the need for travel to perform a living or education in young people, their little experience of driving, unnecessary acceleration, and finally inadequate knowledge of traffic rules and regulations (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous clinical examination and necessary initial interventions can prevent two major traumatic complications, namely neurogenic shock and spinal shock in spinetraumatic patients [3,7]. Since, a solid understanding of injury mechanisms and using an optimal emergency management pattern, including the prevention of secondary injuries by prompt patient's transference to an appropriate trauma center, are mainly sought in the care of patients with traumatic spine, the critical role of prehospital intensive care is the first step of traumatic care system [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Road traffic injuries (RTIs) are the main causes of early death, disability and a major health issue in low and middle-income countries[1]. RTIs are the cause of deaths, financial losses, and preventable health threats, even in developed countries [2]. It has been reported that most victims of RTIs are people aged <50 years old[3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that most victims of RTIs are people aged <50 years old[3]. RTIs are the second leading cause of death from fatal injuries in Iran [2]. According to the World Health Organization (WHO), Iran had an RTI mortality rate of 34.1 deaths per 100,000 in 2013 [4] and had the third-highest rate of fatal RTIs in 2015 [5].…”
Section: Introductionmentioning
confidence: 99%